2012
DOI: 10.1590/s0103-84782012005000128
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade genética de acessos da cultivar ‘BRS Bela’ de Stylosanthes guianensis usando marcadores moleculares RAPD

Abstract: IVVariabilidade genética de acessos da cultivar 'BRS Bela' de Stylosanthes guianensis usando marcadores moleculares RAPD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
3
1
Order By: Relevance
“…The results observed here for grouping by the Tocher method diverge from those of studies carried out with Stylosanthes accessions, which also used the UPGMA method (KARIA, 2008;DATE et al, 2010;MATIDA et al, 2013) and where the resulting groups correlated with the botanical varieties. The small differences regarding the formation of the two groupings can be partly explained by the criteria adopted for separation by each of the methods (ELIAS et al, 2007;CRUZ et al, 2012;LIMA et al, 2012).…”
Section: Figurecontrasting
confidence: 99%
“…The results observed here for grouping by the Tocher method diverge from those of studies carried out with Stylosanthes accessions, which also used the UPGMA method (KARIA, 2008;DATE et al, 2010;MATIDA et al, 2013) and where the resulting groups correlated with the botanical varieties. The small differences regarding the formation of the two groupings can be partly explained by the criteria adopted for separation by each of the methods (ELIAS et al, 2007;CRUZ et al, 2012;LIMA et al, 2012).…”
Section: Figurecontrasting
confidence: 99%
“…It can be stated that 95% of the (full-siblings;Sinclair et al, 2014). The occurrence of such outcrossing could be due to the behavior of pollinizers that systematically visit neighboring plants and nonsynchronism in the fluorescence of parental individuals (Matida et al, 2013). In our results, the r p rate revealed that 4.5% of crosses originated from full-sibling families.…”
Section: Outcrossing Systemmentioning
confidence: 47%
“…The basic information includes the mode of reproduction and outcrossing rates, which will be crucial to guide the breeding programs and the conservation of germplasm (Matida et al, 2013). The basic information includes the mode of reproduction and outcrossing rates, which will be crucial to guide the breeding programs and the conservation of germplasm (Matida et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation